The Industry Expertise Channel in Mortgage Lending - Chu, Yongqiang; Xiao, Zhanbing; Zheng, Yuxiang (Journal of Financial and Quantitative Analysis, 2026)
We show that banks use industry knowledge acquired through corporate lending in mortgage lending, a phenomenon we refer to as the “industry expertise channel.” Specifically, banks that specialize in particular industries expand their mortgage lending activity in regions where those industries are concentrated. The impact of industry expertise increases with information asymmetry and borrower risk. In addition, mortgages originated from this channel contain more soft information and perform better. The effect of the channel increases after unexpected industry distress and the 2008 financial crisis, suggesting that the effect is likely causal.